When English Isn’t Enough: Exploring the Emotional and Professional Dilemmas of English Teachers Using Translanguaging in Multilingual Classrooms - Biri, Alprince King; Arilin, Abnir; Rasdi, Anarika; Dawami, Marlyn; Usman, Katrina; Teh, Aprilyn; Bakilan, Hadija; Ishmael, Ismayra; Asiri, Nuzul Ida; Nassal, Fatima Junara (Journal of Cultural Analysis and Social Change, 2026)
This qualitative study explored the lived experiences of English language teachers employing translanguaging as a pedagogical strategy in multilingual classrooms. Specifically, it aimed to (1) examine the emotional and professional experiences of teachers when using translanguaging, and (2) understand the psychological and pedagogical challenges they encounter in balancing institutional expectations with classroom realities. Ten (10) English teachers from senior high school were purposively interviewed, and data were analyzed thematically. Findings revealed that translanguaging elicited a range of emotions, including relief, connection, guilt, and self-doubt, while also fostering professional adaptability and confidence. Teachers reported challenges related to policy constraints, fear of judgment, and difficulty maintaining a balance between language immersion and comprehension. Coping strategies included rationalizing translanguaging as a pedagogical necessity, adaptive teaching, seeking validation through student outcomes, and emotional detachment. The study concludes that translanguaging, when strategically employed, supports student learning, strengthens teacher agency, and contributes to professional growth. These insights contribute to understanding the interplay between teacher identity, pedagogy, and institutional expectations in multilingual educational contexts.